IMPROVEMENT OF DIALOGICAL SKILLS AND STUDENTS' SKILLS IN FOREIGN LANGUAGE LESSONS - H.M. Pedosyuk (Academy of Cognitive and Natural Sciences, 2007)
The article deals with the peculiarities of the use of teaching dialogue while learning the English language. The author gives examples of the trainings purposed to improve pupils' dialogue skills at the lessons of learning new material.